In vitro anthelmintic activity of the extract of coffee husk fermented with Pleurotus ostreatus for Ascaridia galli - Badarina, Irma; Putranto, Heru Dwi; Sulistyowati, Endang (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2017)
The objective of this research was to evaluate the anthelmintic efficacy of the ethanolic and aqueous extract of coffee husk fermented by Pleurotus ostreatus against Ascaridia galli. In vitro study of anthelmintic activity was conducted by counting the number of paralyzed worm body of Ascaridia galli during 24 hours in petri dish containing different levels of ethanolic and aqueous extract of fermented coffee husk, namely 0%, 1%, 2%, 3% and 4% (w/v) and compared to piperazine 0,5% (w/v) and NaCl 0,9%. The powdered samples of fermented coffee husk were macerated in the 30% ethanol solution with the ratio samples to solution = 1:3. In aqueous extract, samples to solution ratio was 1 : 7. The extract of fermented coffee husk possess phytochemical compunds which responsible for anthelmintic activity. The anthelmintic activity of ethanolic extract was better than aqueous extract. Fermented coffee husk ethanolic extract exhibited mortality of A.galli at concentration 2% while showed highest mortality at concentration 4%. Fermented coffee husk ethanolic extract have the potential to aid in the control of gastro intestinal parasites in animal